2018
DOI: 10.1177/1524839918770205
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Approach to HIV Prevention in Rural Guatemala

Abstract: This research informs refinement of a culture-specific intervention prioritizing indigenous Mayans. We highlight how community-based research and engagement enhance community health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most studies on stigma in Guatemala focus on how HIV/AIDS stigma intersects with preexisting stigma around sexual orientation, gender identity, sex work, migrant status, and social class within larger structures of inequality (Bartels et al, 2023;Infante et al, 2009;Rocha-Jiménez et al, 2018). These studies demonstrate how anticipated, enacted, and internalized stigmas contribute to the loss of family and social support, isolation from religious communities, discrimination in health care settings, and mental distress (Boyce et al, 2012;Miller et al, 2020;Orrego Dunleavy et al, 2018;Rhodes et al, 2015). Using national data, Hackman et al (2016) showed how body size stigma, enacted through weight teasing, contributes to mental distress among women.…”
Section: Mental Health In Guatemalamentioning
confidence: 99%
“…Most studies on stigma in Guatemala focus on how HIV/AIDS stigma intersects with preexisting stigma around sexual orientation, gender identity, sex work, migrant status, and social class within larger structures of inequality (Bartels et al, 2023;Infante et al, 2009;Rocha-Jiménez et al, 2018). These studies demonstrate how anticipated, enacted, and internalized stigmas contribute to the loss of family and social support, isolation from religious communities, discrimination in health care settings, and mental distress (Boyce et al, 2012;Miller et al, 2020;Orrego Dunleavy et al, 2018;Rhodes et al, 2015). Using national data, Hackman et al (2016) showed how body size stigma, enacted through weight teasing, contributes to mental distress among women.…”
Section: Mental Health In Guatemalamentioning
confidence: 99%